Preferensi Nasabah Funding terhadap Bank Muamalat Indonesia Cabang Yogyakarta: Funding Customer Preferences toward Bank Muamalat Indonesia Yogyakarta Branch - M.F. Hidayatullah (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2018)
The Islamic banking industry in Indonesia faces intense competition and a vast floating market, yet its market share remains very low, making it crucial to understand what drives customer preferences. This study is grounded in the theory of consumer behavior and marketing strategy, specifically focusing on factors influencing funding customers' choices in Islamic banks. The research aims to identify and analyze the factors affecting funding customer preferences at Bank Muamalat Indonesia (BMI) Yogyakarta Branch and to determine the most dominant factor. A quantitative descriptive method was employed, involving 100 respondents selected through simple random sampling from a population of 2,531 customers. Data were collected using a Likert-scale questionnaire, and validity and reliability tests were conducted using SPSS version 11.0. The analysis utilized Chi-Square goodness-of-fit tests. The findings reveal that five factors significantly influence customer preferences: security, economic benefits, service, religious compliance, and promotion. Among these, the religious factor has the strongest influence (Chi-Square value of 288.480), followed by service, security, promotion, and economic factors. The study concludes that while religious adherence is the primary driver for choosing BMI Yogyakarta, non-religious factors collectively account for over 50% of preferences, recommending that bank management should maintain sharia compliance while also improving service quality, security, and promotional strategies to attract more rational customers. Industri perbankan syariah di Indonesia menghadapi persaingan ketat dan pasar melayang yang besar, namun pangsa pasarnya masih sangat rendah, sehingga penting untuk memahami faktor-faktor yang mendorong preferensi nasabah. Penelitian ini dilandasi oleh teori perilaku konsumen dan strategi pemasaran, dengan fokus pada faktor-faktor yang mempengaruhi pilihan nasabah funding di bank syariah. Penelitian ini bertujuan mengidentifikasi dan menganalisis faktor-faktor yang mempengaruhi preferensi nasabah funding di Bank Muamalat Indonesia (BMI) Cabang Yogyakarta serta menentukan faktor yang paling dominan. Metode kuantitatif deskriptif digunakan dengan melibatkan 100 responden yang dipilih melalui simple random sampling dari populasi 2.531 nasabah. Data dikumpulkan menggunakan kuesioner skala Likert, dan uji validitas serta reliabilitas dilakukan dengan SPSS versi 11.0. Analisis menggunakan uji keselarasan Chi-Square. Hasil penelitian menunjukkan bahwa lima faktor berpengaruh signifikan: keamanan, ekonomi, layanan, religius, dan promosi. Faktor religius merupakan yang paling dominan (nilai Chi-Square 288,480), diikuti layanan, keamanan, promosi, dan ekonomi. Kesimpulannya, meskipun faktor religius menjadi pendorong utama, faktor non-religius secara kolektif mempengaruhi lebih dari 50% preferensi. Rekomendasi bagi manajemen bank adalah tetap menjaga kepatuhan syariah sekaligus meningkatkan kualitas layanan, keamanan, dan strategi promosi untuk menarik nasabah yang semakin rasional.